Four additional natural 7-deazaguanine derivatives in phages and how to make them - Cui, Liang (2024)
Bacteriophages and bacteria are engaged in a constant arms race, continually evolving new molecular tools to survive one another. To protect their genomic DNA from restriction enzymes, the most common bacterial defence systems, double-stranded DNA phages have evolved complex modifications that affect all four bases. This study focuses on modifications at position 7 of guanines. Eight derivatives of 7-deazaguanines were identified, including four previously unknown ones: 2'-deoxy-7-(methylamino)methyl-7-deazaguanine (mdPreQ1), 2'-deoxy-7-(formylamino)methyl-7-deazaguanine (fdPreQ1), 2'-deoxy-7-deazaguanine (dDG) and 2'-deoxy-7-carboxy-7-deazaguanine (dCDG). These modifications are inserted in DNA by a guanine transglycosylase named DpdA. Three subfamilies of DpdA had been previously characterized: bDpdA, DpdA1, and DpdA2. Two additional subfamilies were identified in this work: DpdA3, which allows for complete replacement of the guanines, and DpdA4, which is specific to archaeal viruses. Transglycosylases have now been identified in all phages and viruses carrying 7-deazaguanine modifications, indicating that the insertion of these modifications is a post-replication event. Three enzymes were predicted to be involved in the biosynthesis of these newly identified DNA modifications: 7-carboxy-7-deazaguanine decarboxylase (DpdL), dPreQ1 formyltransferase (DpdN) and dPreQ1 methyltransferase (DpdM), which was experimentally validated and harbors a unique fold not previously observed for nucleic acid methylases.